Active Endoscope Preserving Image Orientation for Endonasal Skull Base Surgery - Geunwooong Ryu; Chulmin Park; Kim Jeongryul; Keri Kim (42ND ANNUAL INTERNATIONAL CONFERENCES OF THE IEEE ENGINEERING IN MEDICINE AND BIOLOGY SOCIETY: ENABLING INNOVATIVE TECHNOLOGIES FOR GLOBAL HEALTHCARE EMBC'20, 2020)
Endonasal Skull Base Surgery has some advantages over conventional methods; however, some issues such as the need to replace the endoscope due to the fixed view, and possible invasiveness during insertion make the procedure difficult. To solve these problems, this paper proposes an active endoscope mechanism with several benefits. First, its variable direction of view can cover the wide ranges. Second, it provides a forward view, lessening the danger of damaging critical tissues while the endoscope is being inserted. Third, it can change the direction of view within a very small radius of 6.5 mm, so it can be used in a small cavity and work together with other surgical tools. We have designed the endoscope, which has 4 mm diameter. It is a simple tilting and rotation mechanism of 2-degree of freedom (DOF). It implements kinematics control to make it intuitive to operate. The image sensor attached to the distal end is fixed mechanically so that the image orientation is preserved in the direction of gravity. The experiments showed the user could intuitively control the endoscope with the master device and observe the target without swapping the endoscope. Future tests will examine clinical aspects and combination work with surgical instruments.